The Influence Of Work-Life Balance, Communication, And Leadership On Employee Performance At PT. Multi Artha Semesta - Ismailani, Fira; Hasibuan, Hasrul Azwar; Yanti, Eli Delvi (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of work life balance, communication, and leadership on employee performance at PT. Multi Artha Semesta. The research employs a quantitative approach using a causal method to examine the cause-and-effect relationships among variables. The population of this study consists of all front office employees of PT. Multi Artha Semesta, totaling 53 employees, who were all selected as the sample using a saturated sampling technique. Data were collected through questionnaires measured using a Likert scale and analyzed with the assistance of SPSS software. Data analysis techniques included validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that work life balance, communication, and leadership partially have a positive and significant effect on employee performance. Furthermore, the simultaneous test results show that all independent variables collectively have a significant influence on employee performance. These findings suggest that a balanced work and personal life, effective communication, and good leadership play an important role in improving employee performance in the hospitality industry. Therefore, it is recommended that the company enhance work life balance policies, improve internal communication quality, and apply supportive leadership practices to improve employee performance and service quality.